Export Information Use - Diamantopoulos, Adamantios (Emerald Publishing Limited, 2003)
The importance of information as a key factor influencing a firm's export behavior has long been acknowledged in the international marketing literature. Indeed, a common feature of empirical studies on such diverse issues as export initiation and expansion, export barriers, export market orientation, utilization of export assistance, and market/country selection and assessment is that they have all highlighted the critical role of information in export decision making (see, for example, Johanson and Vahlne, 1977; Leonidou, 1995; Cadogan et al.